Damage signals in the insect immune response - Krautz, Robert; Arefin, Badrul; Theopold, Ulrich (Frontiers in Plant Science, 2014)
Insects and mammals share an ancient innate immune system comprising both humoral and cellular responses. The insect immune system consists of the fat body, which secretes effector molecules into the hemolymph and several classes of hemocytes, which reside in the hemolymph and of protective border epithelia. Key features of wound- and immune responses are shared between insect and mammalian immune systems including the mode of activation by commonly shared microbial (nonself) patterns and the recognition of these patterns by dedicated receptors. It is unclear how metazoan parasites in insects, which lack these shared motifs, are recognized. Research in recent years has demonstrated that during entry into the insect host, many eukaryotic pathogens leave traces that alert potential hosts of the damage they have afflicted. In accordance with terminology used in the mammalian immune systems, these signals have been dubbed danger- or damage-associated signals. Damage signals are necessary byproducts generated during entering hosts either by mechanical or proteolytic damage. Here, we briefly review the current stage of knowledge on how wound closure and wound healing during mechanical damage is regulated and how damage-related signals contribute to these processes. We also discuss how sensors of proteolytic activity induce insect innate immune responses. Strikingly damage-associated signals are also released from cells that have aberrant growth, including tumor cells. These signals may induce apoptosis in the damaged cells, the recruitment of immune cells to the aberrant tissue and even activate humoral responses. Thus, this ensures the removal of aberrant cells and compensatory proliferation to replace lost tissue. Several of these pathways may have been co-opted from wound healing and developmental processes.